Virulence potential of new bacterial species associated with entomopathogenic nematodes isolated from soil of Punjab - Kaur, Rajwinder; Jindal, Vikas (Indian Journal of Plant Protection, 2020)
Xenorhabdus and Photorhabdus spp. are symbiotic bacteria of entomopathogenic nematodes (EPN) that produce insecticidal toxins for the control of wide range of insect pest. The aim of this study was to isolate and characterize the bacteria associated with five local strains of EPN (N-12, N-13, N-14, N-15 and N-17) from soil in Punjab. The 16S rDNA from each bacterial species was amplified, gel purified and cloned in sequencing vector. The nucleotide sequence of 16 Sr DNA was determined and edited using bioinformatic software. The bacterial isolates were identified based on nucleotide sequence homology with the available database in NCBI. Sequence similarity analysis revealed that the bacterial isolate 1 is quite close to Delftia acidovorans, isolate 2 to Brucella spp., isolate 3 to Pantoea dispersa and isolate 4 and 5 to Chryseobacterium culicis. The phylogenetic tree established that all the bacterial isolates were different from most commonly occurring symbiotic bacteria (Xenorhabdus and Photorhabdus) associated with EPNs. All the bacterial isolates were tested for their virulence against Spodoptera litura at 105, 106 and 107 cells/ml. None of the bacterial isolates at the tested concentrations was found pathogenic to S. litura.